Pleomorphic lobular carcinoma in situ of the breast: clinicopathological review of 47 cases. Issue 7 (25th February 2014) - Khoury, Thaer; Karabakhtsian, Rouzan G; Mattson, David; Yan, Li; Syriac, Susanna; Habib, Fadi; Liu, Song; Desouki, Mohamed M
<x xml:space="preserve">Abstract</x> Aims Pleomorphic lobular carcinoma in situ (PLCIS) of the breast is a distinctive entity, but its behaviour and management are unclear. The purpose of this study was to review a relatively large number of cases and to evaluate the risk of recurrence. Methods and results Cases of PLCIS (n = 47) from a 12‐year period were reviewed. The clinical, radiological and pathological findings were recorded. Immunohistochemistry for oestrogen receptor (ER), progesterone receptor (PR) and HER2 was performed. Thirty‐one patients had no concurrent breast cancer or past history of breast cancer, and six (19.4%) of these had local recurrence; all tumours (four invasive carcinoma and two PLCIS) were ipsilateral. Younger age at presentation was a risk factor for local recurrence: patients with recurrence had a mean age (range) of 52.5 years (44–59 years), versus 60.6 years (40–81 years) for those without (P = 0.03). Three of 31 patients were treated with radiation therapy (RT), and none of these developed local recurrence. PLCIS had an adverse ER/PR/HER2 molecular profile, with at least 41.2% of the cases overexpressing HER2. Moreover, at least 11.7% of the cases were triple‐negative. Conclusions This study included the largest number of patients who had no concurrent breast cancer or past history of breast cancer with the longest clinical follow‐up, providing insights into management practices for PLCIS and the risk of recurrence.